(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2025)
The study comprehensively characterized Lipoblepharis urticifolia (syn. Wedelia urticifolia) leaves, focusing on elucidating the phytochemical composition of their essential oil, assessing the antioxidant and antidiabetic activities of its methanolic leaf extract. The study also involved a detailed pharmacognostic analysis of macroscopic, microscopic, fluorescence, and physicochemical properties. The essential oil was found to contain 17 individual chemical components through a gas chromatography-mass spectrometry (GC-MS) study, predominantly octadecanoic acid ethenyl ester (69.28%), followed by β-Caryophyllene (7.54%) and β-elemene (4.05%). The methanolic extract of L. urticifolia leaves demonstrated dose-dependent total antioxidant capacity with increasing absorbance observed in the phosphomolybdate assay. Furthermore, it exhibited significant nitric oxide scavenging activity, showing an IC50​ of 29.10μg/ml comparable to the standard Vitamin C (IC50​=18.25μg/ml). Pharmacognostic analysis characterized L. urticifolia leaves as bitter, ovate, and serrated with bristly hairs; quantitative microscopy revealed a stomatal index of 33.1%, trichome index of 23.3%, and vein islet/termination numbers of 1 per mm2. Powder microscopy confirmed anomocytic stomata and uniseriate non-glandular trichomes, complemented by varied UV fluorescence. Physicochemical analysis revealed low moisture, high acid-soluble ash, superior methanolic extract yield and abundant K, Ca, Na, detectable Fe and P. This research offers crucial data for authenticating, identifying, and assessing the therapeutic potential of L. urticifolia.